Eyes like it, Brain Likes it: Tracking the Neural Tuning of Cultural Diversity in Eye Movements for Faces - Lao, Junpeng (Iperception, 2011)
Eye movement strategies deployed by humans to identify conspecifics are not universal. Westerners preferentially fixate the eyes and the mouth during face recognition, whereas strikingly Easterners focus more on the face central region. However, when, where and how Preferred Viewing Locations (PVLs) for high-level visual stimuli are coded in the human brain has never been directly investigated. Here, we simultaneously recorded eye-movements and electroencephalographic (EEG) signals of Westerners and Easterners during face identification of learnt identities. After defining 9 equidistant Viewing Positions (VPs) covering all facial internal features, we presented the learned faces centered on a random VP for 100ms. We then extracted from prior free-viewing fixation maps the average Z-scored fixation intensity for the nonoverlapping facial VP regions (VPZs). Finally, we computed a component-free data-driven spatio-temporal regression between the VPZs and EEG amplitudes. This analysis revealed a universal direct relationship between VPZ and EEG amplitudes over the face-sensitive N170 network at around 350ms, an effect unrelated to a burst of microsaccades occurring in this time-window. Our data show that the distinct cultural fixation preferences for faces are related to a universal post-perceptual tuning in the occipito-temporal cortex. Culture shapes visual information sampling, but does not regulate neural information coding.